Electron Paramagnetic Resonance Study of the Fractions and Trapped Compounds in Asphaltenes of Merey Heavy Crude Oils and Its Vacuum Residue - Hernandez Nuñez, Maury Sabrina (2020)
The electron paramagnetic resonance (EPR) technique was used to study the behavior of the asphaltenes from the Merey crude oil (ASCM), its vacuum residue (ARVM), its fractions, and trapped compounds (A1-ASCM, A2-ASCM, TC-ASCM, A1-ARVM, A2-ARVM, and TC-ARVM). Asphaltenes were precipitated from Merey heavy crude oil and its vacuum residue. The fractionation of our petroleum asphaltenes was carried out using the para-nitrophenol (PNP) method. Two fractions named A1 and A2 and trapped compounds were obtained. The temperature dependence of the EPR spectra was used to obtain a set of temperatures related to free radical (FR) generation and recombination. From the analysis of the EPR spectrum of the most intense signal of the vanadium, we obtain the temperature ranges of the anisotropic-to-isotropic domains, we found a nonlinear behavior of the B parameter in the temperature range studied, and we propose a functional relationship for this parameter as a function of the temperature. On the other hand, we found the temperatures for the slow-to-fast motion regime in these samples and correlated it with the mobility of the fractions.